DARI TIKTOK KE KELAS: TRANSFORMASI SUMBER BELAJAR BAHASA INDONESIA DI KALANGAN SISWA - I Gusti Agung Widya Savitri; Ni Kadek Cintya Dwi Arianti; Ni Kadek Vina Maharani; MG Rini Kristiantari; Chindytia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of digital technology has driven a transformation of learning resources from conventional forms to social media–based platforms, including in Indonesian language learning. TikTok, initially known as an entertainment platform, has evolved into a learning resource utilized by students. This study aims to analyze the transformation of TikTok as a learning resource, its impact on students’ language skills, and the challenges in its implementation. The method used is a literature review by analyzing various academic journals related to digital media and language learning. The findings indicate that TikTok contributes to improving vocabulary acquisition, communication skills, and student engagement through short and interactive video content. In addition, its use encourages a shift in students’ roles to become more active and creative in the learning process. However, several limitations exist, such as the lack of depth in content delivery, the use of informal language that does not adhere to standard rules, and potential distractions from non-educational content. Therefore, appropriate strategies, strengthened digital literacy, and active teacher guidance are required to ensure its effective use. In conclusion, TikTok has significant potential as an innovative learning resource, but it must be used in a directed manner to optimally support Indonesian language learning.